META-ANALYSIS OF THE EFFECT OF MAKE A MATCH LEARNING MODEL ON PRIMARY SCHOOL STUDENTS LEARNING OUTCOMES - Lahma Ainun Sajidah; Mohammad Taufiq; Muhammad Thamrin; Sri Hartatik (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aims to determine the effect of the Make a Match learning model on learning outcomes of primary school students. The method used in this research was meta-analysis method. This study was to determine whether the Make a Match learning model can improve student learning outcomes. The data were collected through relevant article. The data was obtained from online journal searches through Google Scholar, where 10 articles were obtained. The keywords used are